FAKTOR-FAKTOR YANG MEMPENGARUHI IBU DALAM MEMILIH METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KECAMATAN BUKIT KABUPATEN BENER MERIAH TAHUN 2024 - Mustiara, Mauli; Arami, Nova; HS, Nurlaely (Akper Kesdam I/Bukit Barisan Padang, 2024)
ABSTRACTSimpang Tiga Health Center is one of the community health service centers, especially in Bukit District. Based on the number of active family planning participants in 2023, the number of PUS is 4,913, with non-MKJP users amounting to (76.2%) and MKJP users amounting to (23.8%). Formulation of the problem for this research: Are there factors that influence mothers in choosing long-term contraceptive methods (MKJP). The aim of this research is to determine the relationship between the level of knowledge, education and husband's support in choosing a long-term contraception method (MKJP) in the work area of Simpang Tiga Health Center in 2024. Long-term contraceptive methods (MKJP) are contraceptives that are known to have a high level of effectiveness for delaying or managing pregnancy because they can protect against the risk of pregnancy over a long period of time and have a low failure rate. This research method was carried out using a quantitative approach using a cross-sectional design. The sampling technique in this research was Accidental Sampling of 90 respondents. The results of the research show that knowledge has a p-value = 0.003 < 0.05, education has a p-value = 0.009 > 0.0, and husband's support has a p-value = 0.000 > 0.05, which means knowledge, education and support Husbands have an influence on the choice of long-term contraceptive methods (MKJP). The conclusion of this researcher is that knowledge, education and husband's support influence the choice of long-term contraceptive methods (MKJP). It is hoped that from the results of this research, the community as family planning participants and husbands will have to play a greater role in determining the choice of contraceptive method use. Keywords : MKJP Selection Factors